2000
DOI: 10.1038/sj.jp.7200296
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen Use to Reduce the Incidence and Severity of Bronchopulmonary Dysplasia: A Pilot Study

Abstract: Although a trend toward less ventilator and hospital days in the ibuprofen group was observed in this pilot study, the differences were not statistically significant. The incidence of BPD was similar in both groups. In the study group, two infants developed gastrointestinal complications and a third infant experienced reversible renal failure. The plasma ibuprofen levels were low. Further studies are needed to assess the use of ibuprofen for the prevention and/or treatment of BPD in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
(17 reference statements)
0
15
0
1
Order By: Relevance
“…In the study by Raju et al, 32 in which ibuprofen was administered orally or intravenously to 9 preterm infants for the prevention of bronchopulmonary dysplasia, the study drug was withdrawn in 1 infant after 8 days (15 doses) of treatment because of gastrointestinal hemorrhage that occurred 6 hours after the last dose. However, this infant also received steroids and aminophylline, which potentially can cause gastrointestinal bleeding, and it is not clear whether this infant received intravenous or oral ibuprofen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Raju et al, 32 in which ibuprofen was administered orally or intravenously to 9 preterm infants for the prevention of bronchopulmonary dysplasia, the study drug was withdrawn in 1 infant after 8 days (15 doses) of treatment because of gastrointestinal hemorrhage that occurred 6 hours after the last dose. However, this infant also received steroids and aminophylline, which potentially can cause gastrointestinal bleeding, and it is not clear whether this infant received intravenous or oral ibuprofen.…”
Section: Discussionmentioning
confidence: 99%
“…However, this infant also received steroids and aminophylline, which potentially can cause gastrointestinal bleeding, and it is not clear whether this infant received intravenous or oral ibuprofen. 32 Furthermore, gastrointestinal adverse reactions have been observed among preterm and term infants whose mothers were treated with antenatal indomethacin without direct contact of the nonsteroidal anti-inflammatory drugs with the gastrointestinal tract of the newborn. [35][36][37] Serum creatinine levels in our patients were within normal range at all times, so there was no contraindication for a second or third dose of ibuprofen when it was needed.…”
mentioning
confidence: 99%
“…Meta-analysis has confi rmed that ibuprofen use in preterm infants is associated with an increased incidence of CLD [1] . Also, in a recent small trial of ibuprofen in infants with CLD, the incidence of NEC was increased in the test group [2] .…”
Section: Discussionmentioning
confidence: 93%
“…However, some recent studies have suggested that ibuprofen may be associated with the development of infl ammatory diseases, including necrotizing enterocolitis (NEC) and chronic lung disease (CLD), in premature infants [1,2] . These conditions are preceded by infection and/or tissue hypoxia, and are characterized by elevated levels of infl ammatory mediators that reduce the rate of neutrophil apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from steroids, ibuprofen and cromolyn have been assessed for the prevention and treatment of BPD; however clinical studies have shown them to be ineffective [8,9]. Experimental studies using pentoxifylline have demonstrated suppressed synthesis of tumor necrosis factor (TNF) and granulocyte-macrophage colony stimulating factor (GM-CSF) by human monocytes and lung macrophages [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%